IMPLEMENTASI MEDIASI PENAL DALAM PENYELESAIAN TINDAK PIDANA PENGRUSAKAN (Studi Pada Sat Reskrim Polres Solok) - Nursin, Hendri; Fitriati, Fitriati (LPPM Universitas Ekasakti Padang, 2019)
Penal mediation is one of the means of resolving criminal acts that have often been carried out by law enforcement officials, especially at the level of investigations in the police as explained in the letter of the Chief of Police No: B / 3022 / XII / 2009 / SDEOPS, December 14, 2009 concerning Handling Case Through Alternative Dispute Resolution (ADR). Specifications in this study are descriptive analytical. The reason mediation model carried out by the Aro police station The likes of resolving criminal cases are mediation victim-offender models. This model places more emphasis on mediation between victims and perpetrators involving various parties who meet. The mediator can come from a formal official, independent mediator or combination. In this case the mediators involved were ninik mamak and local adat stakeholders and even the Kerapatan Adat Nagari (KAN). The obstacle encountered in the reasoning mediation of the Aro Suka police station is that there is no explicit regulation as a legal aspect governing reason mediation in the settlement of criminal cases, then the Police cannot fully act as mediators in the settlement of criminal cases through reasoning mediation, and there are still some people argues that all criminal cases can be carried out reason mediation or peace efforts between litigants. The effort that must be made is to encourage customary institutions in the nagari along with their traditional leaders to assist the National Police in resolving criminal cases whose source of problems starts from the issue of inheritance, inheritance, customary titles and so on.